Examining the relationship between dynamic balance skill and reactive agility performance in karate athletes - Kocahan, T.; Güraslan, H.; Kabak, B.; Hasanoglu, A.; Akinoglu, B. (Turkish Journal of Sport and Exercise, 2022)
The aim of this study is to examine the relationship between dynamic balance ability and reactive agility performance in karate athletes. A total of 53 karate athletes, 19 females (35.8%) 34 males (64.2%), (mean age: 18.02 ± 1.60 years, mean height 172.13 ± 7.59 cm; mean body weight 64.83 ± 9.75 kg) were included. Dynamic balance ability was tested in three directions: anterior, posterolateral and posteromedial using the "Y Balance Test" platform. Reactive agility performance was evaluated in a SpeedCourt ™ system in a closed space. Pearson or Spearman correlation analysis was used according to the distribution status to examine the relationship between the variables. Statistical error level was determined as p<0.05. It was determined that there was a positively weak and moderate correlation between the dynamic balance ability of the athletes and their reactive agility performance (r = 0.273 / 0.565, p <0.05). As a result of our study, it was determined that karate athletes with good dynamic balance ability had good agility performance. Having good dynamic balance skill indicates that the athlete has less postural oscillation and more stabilization. We think that this situation will contribute to better reactive agility activities that require constant change of direction. As a result of our study, it is recommended to consider dynamic balance elements in improving reactive agility performance in karate athletes.